Phorbol myristate acetate induces the secretion of an elastase by populations of resident and elicited mouse peritoneal macrophages - Dahlgren, Mary Ellen; Davies, Philip; Bonney, Robert J. (Biochimica et biophysica acta, 1980)
Cultured thioglycollate-elicited mouse peritoneal macrophages secrete an enzyme which hydrolyzes [ 3H]elastin prepared by NaB 3H 4 reduction of bovine ligamentum nuchae elastin. Over a 24 h culture period, 3.5 · 10 6 thioglycollate-elicited cells secrete sufficient enzyme to solubilize 200–350 μg [ 3H]elastin in 18 h. Secretion at this rate continues for at least 6 days in culture. Secretion of the enzyme is stimulated 3-fold by exposure of the cultured cells to 10 −7 M phorbol myristate acetate, whereas the parent alcohol 4α-phorbol is inactive in this respect. Enzyme activity is linearly related to the amount of conditioned medium assayed and is linear over incubation times up to 30 h. Unlabelled elastin competitively inhibits the solubilization of [ 3H]elastin. The solubilization rate is doubled if the substrate is pretreated with sodium dodecyl sulfate, but the rate of solubilization of this pretreated substrate increases with time. Resident peritoneal macrophages secrete barely detectable amounts of elastase, but phorbol myristate acetate (10 −7 M) stimulates its secretion in amounts comparable to those secreted by phorbol myristate acetate-stimulated thioglycollate-elicited cells. Dexamethasone (10 −9 M) inhibits phorbol myristate acetate-induced secretion by 50%, but 10 −6 M indomethacin is without effect. The secreted enzyme has the characteristics of a metalloproteinase.